Effects of the 2018 Martian Global Dust Storm on Boundary Positions in the Induced Magnetosphere - Catherine E. Regan; Andrew J. Coates; Mark Lester; Anne Wellbrock; Geraint H. Jones; Beatriz Sánchez-Cano; Philippe Garnier; Louisa J. Preston; František Němec; Václav Linzmayer; Rudy A. Frahm; Mats Holmström (The Planetary Science Journal)
Global dust storms at Mars have a significant impact on the atmosphere and ionosphere, but only recently has their impact on the magnetosphere been investigated. The 2018 global dust storm at Mars was the first global event following the arrival of the Mars Atmosphere and Volatile EvolutioN mission at Mars, providing additional data to that of Mars Express observing how plasma boundaries (the bow shock and induced magnetospheric boundary (IMB)) varied over the storm duration. Applying 2D boundary models to spacecraft crossings, we find that the variability of both boundaries increases due to the storm onset and continues after surface conditions have returned to normal. While the bow shock shows no influence from the crustal magnetic fields in the southern hemisphere of Mars, the IMB dips here, the opposite of its normal bulging behavior. This is consistent with the signature found during the 2007 global dust storm. We suggest this signature is due to a decrease in ionospheric pressure in this area from the transport of ionized particles down crustal magnetic field lines toward the surface of Mars.